2015
DOI: 10.1097/mpa.0000000000000276
|View full text |Cite
|
Sign up to set email alerts
|

The Role of p21-Activated Kinases in Pancreatic Cancer

Abstract: Pancreatic cancer is an aggressive cancer with a poor prognosis and an overall 5-year survival rate of less than 5%. Management has not improved significantly over the last 30 years, and a better understanding of the genetic and molecular changes that occur is urgently required. Many of these changes appear to involve the p21-activated kinases (PAKs). The PAK family consists of 6 isoforms, 2 of which, PAK1 and PAK4, are up-regulated and/or hyperactivated in pancreatic cancer. p21-Activated kinases can mediate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
37
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 148 publications
(182 reference statements)
1
37
0
Order By: Relevance
“…p21 is an important member of the Cip family (8) and the cyclin-dependent kinase inhibitor family (9). A mutation in the p21 gene is associated with pancreatic cancer (10) and the differentiation of other malignant tumor types, including to the depth of invasion, proliferation and metastasis. Additionally, p21 has prognostic value; p21 expression has been documented as a poor prognostic marker in human lung cancer (11).…”
Section: Introductionmentioning
confidence: 99%
“…p21 is an important member of the Cip family (8) and the cyclin-dependent kinase inhibitor family (9). A mutation in the p21 gene is associated with pancreatic cancer (10) and the differentiation of other malignant tumor types, including to the depth of invasion, proliferation and metastasis. Additionally, p21 has prognostic value; p21 expression has been documented as a poor prognostic marker in human lung cancer (11).…”
Section: Introductionmentioning
confidence: 99%
“…Although various functional pathways have been revealed to contribute to the abnormal proliferation during the tumorigenesis of pancreatic cancer, the core trigger for the initiation of pancreatic cancer turns out to be the abnormal intranuclear proliferative regulation [18]. It has been identified that two main biological processes contribute to the abnormal proliferation of pancreatic cells during tumorigenesis: the inhibition of cell apoptosis and the excessive activation of proliferation [19]. All of such regulatory signaling pathways have been reported to be abnormal in pancreatic cancer and further contribute to the tumorigenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several reports [4,9,11,15] unraveled the role of Pak1 in the activation of pancreatic stellate cells (PSCs), its involvement in transforming normal pancreatic cells to PDAC and its ability to modulate drug resistance in pancreatic cancer. All these findings suggest that Pak1-specific inhibitors will prove to be a better adjuvant with the existing chemotherapy modality for PDAC.…”
Section: Expert Opinionmentioning
confidence: 99%
“…As a consequence of this, Pak1 expression pattern in human pancreatic cancer tissues was evaluated and it was found that Pak1 levels are significantly high in PDAC tissue [4,7]. Overexpression and downregulated Pak1 cell line model systems revealed explicit changes in transforming properties, and Pak1 diminished cells failed to form tumors in athymic mice [7].…”
mentioning
confidence: 99%
See 1 more Smart Citation